Analisis Kesalahan Terjemahan Novel “Baina Al-Qasrain” Karya Najîb Mahfûz - Rahmawati, Afifatul; Ananda, Anisa; Suparno, Darsita; Satori, Achmad; Attih, Driss (Universitas Muhammadiyah Gorontalo, 2024)
The background of this study is rooted in the phenomenon that translators often do not adhere to Indonesian language guidelines due to their inability or reluctance to make corrections, as well as their lack of understanding of Indonesian language usage guidelines. The purpose of this study is to apply Indonesian language guidelines in translated texts. The methods used are qualitative methods and analysing the text. Analysing the text through the process of editing words and phrases from the translated text of the novel